Speed estimation and target detection in forward scattering radar - Raja Abdullah, Raja Syamsul Azmir; A. Rasid, Mohd Fadlee; Ismail, Alyani; Mohamed Sadig, Mutaz Salah; Khalafalla, Mohamed (2008)
This paper presents work on target detection and speed estimation method in one of radar types called Forward Scattering Radar (FSR). The problem of extracting the Doppler signature in different interference environments is addressed. Wavelet technique is used to predict the existence of target. For vehicle speed estimation, a new method is proposed, which extracts features from the radar measurements by using a Standard Deviation theory.